Drilling Vanadis 4E with Coated Drills; Examination of Wear, Surface Roughness, and Chip Formation - Salih Korucu; Gürkan Soy; Gürcan Samtaş (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2023)
Vanadis 4E is a versatile powder metallurgical tool steel widely used in today's market with high wear resistance and excellent yield properties. Drilling operations applied to materials are one of the operations commonly used in the machining industry. In drilling operations, coated or uncoated drills are used, which may vary according to the material used. This study applied drilling operation to Vanadis 4E powder metallurgical steel with TiN-coated HSS drills. In the study, Drills with diameters of 5, 8.5, and 10.5 mm, cutting speeds of 22, 23, and 24 m/min, and feed rates of 0.10, 0.12, and 0.14 mm/tooth was used. Nine experiments were carried out using the Taguchi L9 orthogonal array. After the experiments, the material was cut from the holes, and the roughness values were measured from the inner surfaces of the holes. In addition, hardness measurements were made from the material surfaces around the holes. The wear conditions of the drills used in the experiments were examined with an optical microscope after the experiment. The formations after each experiment were also examined. The best roughness value was obtained with the 5 mm diameter drill in the 1st experiment, the best roughness value was obtained in the experiments carried out with the 8.5 mm diameter drill in the 6th experiment, and the best roughness value was obtained in the 7th experiment for the 10.5 mm diameter drill. When the wear in the drills was evaluated, it was observed that the side surface and radial wear occurred.